Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Akuntansi di Kota Surakarta dalam Berkarir Sebagai Akuntan Publik - Nainsi Riana; Banu Witono (Jurnal Akuntansi dan Pajak, 2023)
The financial statements of a corporation must be audited and examined by public accountants. A public accountant's responsibility is to review financial statements. A good public accountant's financial report information may have an impact on a company's reputation. Because there are so few public accountants in Indonesia, accounting students should strongly consider pursuing a career in public accounting. The goal of this study was to examine the variables of monetary benefits, job market accessibility, social values, work environment, professional training, and professional recognition that influence accounting students at Muhammadiyah University of Surakarta's interest in a career as a public accountant. An approach to quantitative research is used in this work.Purposive sampling was the method of sampling employed in this investigation. Using logistic regression analysis, this study's data analysis techniques (logistic regression). The study's findings indicate that societal values, professional training, financial incentive, job market accessibility, and professional reputation only partially affect students' desire in pursuing a career as a public accountant. The work environment is the sole factor that can influence a student's interest in a profession as a public accountant. Keywords : financial rewards, job market availability, social values, work environment, professional training, and professional recognition.